Do Zoo Visitors Attend to Interpretive Elements in Interactive Animal Exhibit Spaces? A Case Study From ZooTampa's Lorikeet Landing Aviary. Issue 2 (November 2022) - Allen, Jessica; Ogle, Brian; Gray, Kerry
This study examined the connection between guest engagement and interactions with provided interpretive elements within an interactive aviary at ZooTampa in Tampa, Florida. Survey data were collected at an interactive aviary where guests are provided the opportunity to feed the birds. Findings demonstrate that guests prefer to interact with a live interpreter versus posted exhibit signage, but interacting with the animals is the strongest indicator of desired outcomes. Furthermore, interactions with exhibit signage were not related to personal feelings of engagement, connection with animal, and enjoyment of watching the birds.